Reheated Palm Oil Consumption and Risk of Atherosclerosis: Evidence at Ultrastructural Level. (19th December 2012) - Xian, Tan Kai; Omar, Noor Azzizah; Ying, Low Wen; Hamzah, Aniza; Raj, Santhana; Jaarin, Kamsiah; Othman, Faizah; Hussan, Farida
Abstract : Background . Palm oil is commonly consumed in Asia. Repeatedly heating the oil is very common during food processing. Aim . This study is aimed to report on the risk of atherosclerosis due to the reheated oil consumption. Material and Methods . Twenty four male Sprague Dawley rats were divided into control, fresh-oil, 5 times heated-oil and 10 times heated-oil feeding groups. Heated palm oil was prepared by frying sweet potato at 180°C for 10 minutes. The ground standard rat chows were fortified with the heated oils and fed it to the rats for six months. Results . Tunica intima thickness in aorta was significantly increased in 10 times heated-oil feeding group (P < 0.05 ), revealing a huge atherosclerotic plaque with central necrosis projecting into the vessel lumen. Repeatedly heated oil feeding groups also revealed atherosclerotic changes including mononuclear cells infiltration, thickened subendothelial layer, disrupted internal elastic lamina and smooth muscle cells fragmentation in tunica media of the aorta. Conclusion . The usage of repeated heated oil is the predisposing factor of atherosclerosis leading to cardiovascular diseases. It is advisable to avoid the consumption of repeatedly heated palm oil.